2008
DOI: 10.1002/macp.200800093
|View full text |Cite
|
Sign up to set email alerts
|

Physical Gelation of Amphiphilic Poly(N‐isopropylacrylamide): Influence of the Hydrophobic Groups

Abstract: The self‐assembling properties of hydrophobically modified (N‐isopropylacrylamide) have been investigated by dynamic light scattering and rheological measurements. Size of the globules and transmission of the solutions vary strongly in the same range of temperature. The presence of hydrophobic groups leads to contraction of the globules' size compared to poly(N‐isopropylacrylamide) (PNIPAM). The viscoelastic properties of the samples in aqueous solution have been investigated as a function of copolymer concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 57 publications
4
17
0
Order By: Relevance
“…Several synthetic polymers that respond to this criteria are known from literature: poly(methyl vinyl ether) [7,8], polyethers [9][10][11][12][13][14], poly(N-vinyl caprolactam) [15], poly [2-(dimethylamino)ethyl methacrylate] [16,17] or poly(N-isopropylacrylamide) (PNIPAM) [18][19][20][21]. PNIPAM is the most studied thermosensitive water-soluble polymers with a LCST of 32°C [18].…”
Section: Introductionmentioning
confidence: 99%
“…Several synthetic polymers that respond to this criteria are known from literature: poly(methyl vinyl ether) [7,8], polyethers [9][10][11][12][13][14], poly(N-vinyl caprolactam) [15], poly [2-(dimethylamino)ethyl methacrylate] [16,17] or poly(N-isopropylacrylamide) (PNIPAM) [18][19][20][21]. PNIPAM is the most studied thermosensitive water-soluble polymers with a LCST of 32°C [18].…”
Section: Introductionmentioning
confidence: 99%
“…Our results correlated well with the study by Wintgens and Amiel, where thermoresponsive PNIPAM was hydrophobically modified with bulky adamantly group. It was observed that sharp transitions occurred in the case of PNIPAMs with low substitution levels (1.4%), in contrast to the broader transitions for PNIPAMs with high substitution levels (4.5%) …”
Section: Resultsmentioning
confidence: 93%
“…Studies have shown that hydrophobic groups can increase the solubility of hydrophobic drugs and the stability of the micelles. 4,5 It also has been reported that the hydrophobic groups can affected the rheological properties of the carrier 6 and the antibacterial activity. 7 Even more the length of hydrophobic groups displayed the decisive effect on the gelation behaviour.…”
Section: Introductionmentioning
confidence: 99%